New Method for Locker Door with Face Security System Using Backpropagation Algorithm - Yusmartato, Y; Lubis, Zulkarnain; Arza, Solly; Pelawi, Zulfadli; Armansah, A; Hasibuan, Abdurrozzaq; Asaad, Mhd. (International Journal of Engineering and Technology, 2018)
Lockers are one of the facilities that people use to store stuff. Artificial neural networks are computational systems where architecture and operations are inspired by the knowledge of biological neurons in the brain, which is one of the artificial representations of the human brain that always tries to stimulate the learning process of the human brain. One of the utilization of artificial neural network is for pattern recognition. The face of a person must be different but sometimes has a shape similar to the face of others, because the facial pattern is a good pattern to try to be recognized by using artificial neural networks. Pattern recognition on artificial neural network can be done by back propagation method. Back propagation method consists of input layer, hidden layer and output layer. Â Â